2011
DOI: 10.1155/2011/172634
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fiber Finish on the Performance of Asphalt Binders and Mastics

Abstract: The objective of this study was to determine the effects of finishes applied to polyester fibers on the properties of asphalt binders and mastics. Asphalt binders were mixed with finishes that were extracted from the fibers, and mastics were also made with binder and fibers (with and without finish) to isolate the effects of the finish. The results indicated that crude source plays a significant role in how the fiber finish affects the binders and mastics. Additionally different finishes had different effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…The abrasion loss value of the control mixture is found to be up to 0.7 percent higher when 0.7 percent steel fiber is added. This indicates that increasing the proportion of steel fiber in a SMA mixture does not improve its abrasion resistance, which is consistent with other researcher findings [7]. Variations in abrasion values, on the other hand, could be caused by a variety of factors, including the angularity of coarse aggregates and uneven compaction force.…”
Section: Cantabro Loss Testsupporting
confidence: 89%
See 2 more Smart Citations
“…The abrasion loss value of the control mixture is found to be up to 0.7 percent higher when 0.7 percent steel fiber is added. This indicates that increasing the proportion of steel fiber in a SMA mixture does not improve its abrasion resistance, which is consistent with other researcher findings [7]. Variations in abrasion values, on the other hand, could be caused by a variety of factors, including the angularity of coarse aggregates and uneven compaction force.…”
Section: Cantabro Loss Testsupporting
confidence: 89%
“…Fiber is a type of polymer that is commonly used as an addition for this purpose [5]. The addition of fibers changes the viscoelasticity of the mixture [6], increases its dynamic modulus [7], improves humidity sensitivity [8], and improves flow coherence, and provides rutting resistance [9,10]. According to the study done by Serin [6], the use of fibers can provide strengthening effect to the application of road pavement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in complex modulus could be due to the fibre affecting the chemical composition of the binder by adsorption/absorption of different fractions, mainly lighter fractions. A previous study, using chromatography, indicated that the fibre could influence the absorption of different fractions, particularly lighter fractions [26]. This result reflects the asphaltene content results, as the asphaltene content increased for drained binder after mixing with fibres, as shown in Table 3.…”
Section: Complex Modulus Master Curve Of Base and Drained Bindersupporting
confidence: 57%
“…Company initiated the first evaluation of asbestos fibers in HMA (5). Results of this study indicated that mixtures containing asbestos fibers illustrated an increase in tensile strength, compressive strength, stability, ability to sustain load after reaching maximum stability, and resistance to weathering.…”
Section: Use Of Fibers In Asphalt Pavementsmentioning
confidence: 99%